Low-Power VLSI Circuits and Systems - Pal, Ajit.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2015)
The book provides a comprehensive coverage of different aspects of low power circuit synthesis at various levels of design hierarchy; starting from the layout level to the system level. For a seamless understanding of the subject, basics of MOS circuits has been introduced at transistor, gate and circuit level; followed by various low-power design methodologies, such as supply voltage scaling, switched capacitance minimization techniques and leakage power minimization approaches. The content of this book will prove useful to students, researchers, as well as practicing engineers.
Introduction -- MOS Fabrication Technology -- MOS Transistors -- MOS Inverters -- MOS Combinational Circuits -- Sources of Power Dissipation -- Supply Voltage Scaling for Low Power -- Switched Capacitance Minimization -- Leakage Power Minimization -- Adiabatic Logic Circuits -- Battery-Aware Systems -- Low Power Software Approaches.
Keywords: Electronic circuits; Electronics; Microelectronics; Computer hardware; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Computer Hardware